Whole-Genome Sequence of Streptomyces pluripotens strain MUM 16J, a Potential Resource of Glycopeptide Antibiotic and Biocontrol Agent against Biofilm-forming Bacteria - Priyia Pusparajah; Jodi Woan-Fei Law; Kok-Gan Chan; Bey-Hing Goh; Kar-Wai Hong; Learn-Han Lee; Loh Teng-Hern Tan (Progress in Microbes and Molecular Biology)
Streptomyces pluripotens strain MUM 16J is a Gram-positive filamentous bacteria isolated from mangrove soil in Kampung Trombol area of Kuching, Sarawak. The draft genome of Streptomyces pluripotens strain MUM 16J consists of 7,671,699 bp assembled into 164 contigs. The GC content of the genome is 70.06 %, and the sequencing coverage of 108×. Its genome consists of 6,781 predicted genes, 6,459 protein-coding genes, and 79 RNA-coding genes (tRNA: 71, rRNA: 8). Here we report the draft genome of this strain to highlight its potential in producing glycopeptide antibiotic as well as catechol, a biocontrol agent of biofilm-producing bacteria.